Production, Purification and Co-crystallization of Plasmodium falciparum and Plasmodium vivax Dihydroorotate Dehydrogenase with Novel Inhibitors for Malaria Therapy - Kago, Leah (My University, 2012)
Malaria remains a world’s disease burden causing high incidences of mortality and morbidity in susceptible populations. Severe cases of malaria mostly caused by parasites of the Apicomplexan Plasmodium falciparum are geographically localized in sub-Saharan Africa whereas less severe malaria but the most prevalent outside of Africa; is caused by parasites of Plasmodium vivax. A malaria campaign through use of effective drugs such as Artemesins-based-Combination Therapies has considerably reduced mortality cases within the past few years. However, increasing incidences of drug resistance have been reported which raises an urgent need for development of new anti-malaria drugs. In-silico drug design using the structure of the biological drug target is the latest lead optimization option in search of more potent drugs. In this study, I sought to determine the 3-dimensional structures of P.falciparum and P.vivax DHODH co-crystallized with novel inhibitors, a putative anti-malaria drug target. For the P.falciparum DHODH whose structure is known, the whole process from site directed mutagenesis and classical cloning, protein over- expression, purification to co-crystallization with an inhibitor was performed, for P.vivax DHODH with no known resolved structure so far, preliminary protein expression studies and purifications steps were achieved. PfDHODH was purified to relative purity yielding viable diffracting crystals co-crystallized with an inhibitor whereas the PvDHODH preliminary studies indicated good protein expression profile with need for further optimization in subsequent steps.
Keywords: Industriell bioteknik; Livsvetenskaper; Industrial Biotechnology; Life Science